2022
DOI: 10.1038/s41598-022-22679-y
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 air and surface contamination in residential settings

Abstract: SARS-CoV-2 transmission occurs mainly indoors, through virus-laden airborne particles. Although the presence and infectivity of SARS-CoV-2 in aerosol are now acknowledged, the underlying circumstances for its occurrence are still under investigation. The contamination of domiciliary environments during the isolation of SARS-CoV-2-infected patients in their respective rooms in individual houses and in a nursing home was investigated by collecting surface and air samples in these environments. Surface contaminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Positive results for SARS-CoV-2 RNA in the air have been found with all the different known methods available, such as filter-based samplers, impingers, impactors, cyclones, water-based condensation, and passive sampling [ 31 34 ]. In the present study, indoor air SARS-CoV-2 particles of the makeshift hospital were sampled simultaneously by two different methods, air sampler and natural sedimentation [ 35 37 ]. The air sampling results of this study showed that 48.19% (80/166) of air samples were positive for SARS-CoV-2 by RT-qPCR, moreover, air samplers (43/60, 71.67%) were more efficient than natural sedimentation (37/106, 34.91%).…”
Section: Discussionmentioning
confidence: 99%
“…Positive results for SARS-CoV-2 RNA in the air have been found with all the different known methods available, such as filter-based samplers, impingers, impactors, cyclones, water-based condensation, and passive sampling [ 31 34 ]. In the present study, indoor air SARS-CoV-2 particles of the makeshift hospital were sampled simultaneously by two different methods, air sampler and natural sedimentation [ 35 37 ]. The air sampling results of this study showed that 48.19% (80/166) of air samples were positive for SARS-CoV-2 by RT-qPCR, moreover, air samplers (43/60, 71.67%) were more efficient than natural sedimentation (37/106, 34.91%).…”
Section: Discussionmentioning
confidence: 99%
“…The development of polymer nanocomposites by using antimicrobial agents in the nanoscale can be an alternative way to avoid this problem. In concern of COVID-19 spreading, such technological approaches to develop self-sanitizing PVC are suitable to avoid the secondary routes of COVID-19 contagion, mainly in hospitals and healthcare clinics that involve touching a contaminated surface and then contamination with dirty hands as extensively reviewed in the literature ( Marquès and Domingo, 2021 ; Correia et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Villafruela et al (2013) numerically investigated the effect of different configurations of air diffusers and exhausts on the transportation of the particles in an isolation room. Correia et al (2022) investigated air and surface contamination in residential environments due to COVID-19. Surface contamination provided the highest positivity/infection rate and persistence for extended periods.…”
Section: Introductionmentioning
confidence: 99%
“…Correia et al. (2022) investigated air and surface contamination in residential environments due to COVID‐19. Surface contamination provided the highest positivity/infection rate and persistence for extended periods.…”
Section: Introductionmentioning
confidence: 99%